Bo med mamma och pappa fast inte tillsammans. Barns perspektiv på växelvis boende – en pilotstudie - Tiverman,Frida; Örneberg,Sofia (2016)
The purpose of this study was to examine attachment linked to self-perception of children living with joint custody. If and why the children contacted the parent they were away from was controlled for, something that has never been examined in research before. All data collected was from the children's point of view and the children (n= 22) participating in the study was between 7-18 years of age, every one of them has had dual residents since early age. The standardized interview (Friends and Family Interview) and the self-assessment form (Self- Perception Profile) were used to examine attachment and self-perception. Results show that half of the children in the study had secure attachment and the other half insecure, a bigger proportion of insecure children compared to general population. The children with secure attachment had their mother, more than the father, as secure base. Significant differences were also found between children with secure and insecure attachment, respectively, regarding their developmental perspective on relationships, their adaptive ability, their parental differentiation and their competence in school and socially. The majority of the children had contact with the parent they were away from. Therefore, living in dual residence early in life seems influence the child’s attachment and the ability to cope with changes in life.
Keywords: växelvis boende; anknytning; FFI; trygg bas; skript; kontakt; självuppfattning; joint physical custody; dual residence; attachment; secure base; contact; script; self-perception